Linguistic Devices for Welcoming, Expansive Learning and Interculturality: Contributions for the Educational Inclusion of Foreign Students [Dispositivos Lingüísticos de Acogida, Aprendizaje Expansivo E Interculturalidad: Contribuciones Para la Inclusión Educativa de Estudiantes Extranjeros] - Hernandez-Yañez, M (Emerson de Pietri, 2020)
In the context of the progressive increase of foreigners in public schools in Chile and the recent changes in migratory patterns, the presence of students who do not master the working language of the educational system has systematically incremented in recent years. In a scenario marked by the absence of educational policies that respond to this new linguistic diversity, the purpose of our research was to understand how schools have responded to the arrival of foreign students and what educational practices they have implemented to tackle this challenge. Through a two-year school ethnography in four public schools with high enrollment of foreigners, institutional documents were analyzed and field observation, interviews and focus groups were conducted with different actors amidst the educational communities. Through an analysis of thematic content, the results reveal the implementation of ten devices to manage educational responses to foreign students. We have analyzed three of these devices with a focus on linguistics based on the tensions and contradictions that occur within the educational institutions of which they are part, identifying significant elements and dimensions to drive forward expansive learning. Finally, we discuss these findings in light of the advances and challenges of the intercultural approach in our Latin American region. © 2020, Emerson de Pietri.